Multirotor UAV-borne Vital Signs Sensing Using 4D Imaging Radar - Zhi LI; Chengyao TANG; Yongpeng DAI; Tian JIN (Leida xuebao)
Unmanned Aerial Vehicle (UAV)-borne radar technology can solve the problems associated with noncontact vital sign sensing, such as limited detection range, slow moving speed, and difficult access to certain areas. In this study, we mount a 4D imaging radar on a multirotor UAV and propose a UAV-borne radar-based method for sensing vital signs through point cloud registration. Through registration and motion compensation of the radar point cloud, the motion error interference of UAV hovering is eliminated; vital sign signals are then obtained after aligning the human target. Simulation results show that the proposed method can effectively align the 4D radar point cloud sequence and accurately extract the respiration and heartbeat signals of human targets, thereby providing a way to realize UAV-borne vital sign sensing.